Effects of Pretreatment for Controlling Internal Water Transport Direction on Moisture Content Profile and Drying Defects in Large-Cross-Section Red Pine Round Timber during Kiln Drying - BATJARGAL, Bat-Uchral; LEE, Taekyeong; CHO, Myungsik; LEE, Chang-Jin; YEO, Hwanmyeong (Journal of the Korean Wood Science and Technology, 2023)
Round timber materials of 600 mm length, cut from large-cross-section round timber of red pine (Pinus densiflora S. et Z.) of 450 mm width and 4.2 m length, were prepared as the target of kiln drying in this study. After treating the target materials through end sealing (ES), end sealing - kerfing (ES-K), lateral sealing - end sealing - boring (LS-ES-B), or lateral sealing - partial end sealing (LS-PES), the effects of the treatment on the incidence of drying defects were determined. The target materials with exposed lateral surface and sealed cross surface were steamed at the initial temperature of 65℃ above the official pest control temperature of 56℃, followed by kiln drying toward the final temperature of 75℃. The target materials with sealed lateral surfaces, on the other hand, were dried at the initial temperature of 90℃ at almost the maximum temperature of conventional kiln drying, as there is no risk of early check formation caused by surface moisture evaporation. The final temperature was set at approximately 100℃. The drying time, taken for the target materials with initial moisture content of 70%–80% to reach the target moisture content of 19%, varied across treatment conditions. The measured drying time was 1,146 hours (approximately 48 days) for the timber with sealed cross surface and 745 hours (approximately 31 days) for the timber with sealed lateral surface, until the moisture content reached the target level. The formation of surface checks could not be prevented in the control and ES groups, but a definite preventive effect was obtained for the LS-ES-B and LS-PES groups. KCI Citation Count: 0